2017
DOI: 10.1002/jsfa.8671
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of influenza virus replication by adlay tea

Abstract: The results of the present study demonstrate that adlay tea had antiviral effects against influenza viruses. Our findings with respect to adlay tea suggest that the polyphenols might have a small influence on its antiviral activity and that other ingredients might have more influence. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 36 publications
(40 reference statements)
2
38
0
Order By: Relevance
“…The FFRA was performed according to a slightly modified version of the previously described method (Nagai, 2018 and Okuno, 1990). MDCK cells (approximately 10 4 cells/well) were seeded in 96‐well flat‐bottom plates (Corning Inc.) and incubated in 5% CO 2 at 37°C to form monolayers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFRA was performed according to a slightly modified version of the previously described method (Nagai, 2018 and Okuno, 1990). MDCK cells (approximately 10 4 cells/well) were seeded in 96‐well flat‐bottom plates (Corning Inc.) and incubated in 5% CO 2 at 37°C to form monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…Based on such previous findings, the present study focused on the anti‐influenza effects of functional foods, such as wild watermelon juice. It has been previously reported that adlay tea is effective against influenza virus (Nagai, 2018), and thus we continued to search for more food extracts that are effective against this virus in the present study (Horio, 2020; Nagai, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Focus formation was induced as described by Nagai et al (8) Each virus dilution was selected to give a final count of approximately 30 focus-forming units (FFU) per well. Virucidal activity was expressed as the reciprocal of the highest dilution that reduced the number of foci to £50% of the control value.…”
Section: Focus Forming Reduction Assay For Virucidal Activitymentioning
confidence: 99%
“…(4)(5)(6)(7) We previously reported that soybean extract exerted antiviral activity against influenza virus growth. (8) During influenza infection, reactive oxygen species (ROS) and lipid peroxides are generated in several tissues such as the lung. (9)(10)(11)(12)(13) Soy isoflavones, such as daidzein, glycitein, and genistein, (14) are a group of compounds present in soybean and function as potent antioxidants.…”
mentioning
confidence: 99%
“…Tea has been consumed for thousands of years as a daily health drink in China and has been traditionally used as a medication based on experience. China and Japan have also described its biological activities including extensive antioxidant and antitumor activities of the active ingredients [2,3]. Ginkgo tea, which is made from ginkgo leaves, is healthy.…”
Section: Introductionmentioning
confidence: 99%